STRATEGI PENGELOLAAN KELAS DALAM MENUMBUHKAN SIKAP DISIPLIN PESERTA DIDIK - Ivana Resti, Amelia; Sari Dewi, Ratna; Rahman Hakim, Zerri; Setiawan, Sigit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The government continues to strive to improve the quality of education through various policies and breakthroughs aimed at realizing the educational goals outlined in the 2013 curriculum. Character education, particularly discipline, is an important aspect of the learning process in elementary schools as the initial level of formal education. Discipline is not only about obeying rules, but also about the ability to manage oneself consistently in thinking, behaving, and acting. Effective classroom management plays a strategic role in fostering student discipline and creating a conducive learning environment. As classroom managers, teachers are required to be able to design, implement, and monitor learning conditions to maintain focus on learning objectives. Therefore, effective classroom management strategies are an important factor in fostering discipline in elementary school students. The purpose of this study was to analyze classroom management strategy planning in fostering discipline, analyze teacher strategy management in fostering discipline in students, and analyze supporting and inhibiting factors in classroom management strategies in fostering discipline in students. This research method used a qualitative method with a descriptive approach. Data collection techniques were carried out through interviews, observation, and documentation. The findings of this study indicate that teachers implement classroom planning systematically by establishing conducive learning. The implementation of classroom management strategies refers to six principles: warmth and enthusiasm, providing challenges, learning variations, flexibility, emphasizing positive aspects, and instilling self-discipline. Supporting factors include principal support, adequate facilities, parental cooperation, responsive student characteristics, an attractive reward system, teacher consistency, school culture, and professional training. Inhibiting factors include differences in family backgrounds, external environmental influences, and a lack of consistency on the part of some parents.